Glacier data - surface elevation from Storglaciären, elevation, 2013-04-17–2020-09-13 - Tarfala Research Station (Stockholm University, 2020)
Tarfala Research Station (2020). Glacier data - surface elevation from Storglaciären, elevation, 2013-04-17–2020-09-13 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/WHzaPM51nx4o-Ro7p9ElKVBW
Keywords: Tarfala Research Station; Atmospheric temperature; Glacier elevation/ice sheet elevation; Glaciers; Relative humidity; Snow depth; Time instant; Time instant; Elevation; Elevation; Air temperature; Air temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap